1990
DOI: 10.1007/978-3-7091-6934-6
|View full text |Cite
|
Sign up to set email alerts
|

Lebensgeschichte der Gold- und Silberdisteln Monographie der mediterran-mitteleuropäischen Compositen-Gattung Carlina

Abstract: Die dadurch begriindeten Rechte, insbesondere die der Ubersetzung, des Nachdruckes, der Entnahme von Abbildungen, der Funksendung, der Wiedergabe auf photomechanischem oder ahnlichem Wege und der Speicherung in Datenverarbeitungsanlagen, bleiben, auch bei nur auszugsweiser Verwertung, vorbehalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…This is borne out in work referred to by Petit (1999), of which we were unaware. Thus, a study of Carlina and Chamaeleon showed the presence of the C-glycosylflavones isovitexin, shaftoside, isoshaftoside, orientin, and unidentified di-C-glycosyl derivatives of apigenin and lute olin variously distributed in members of the two genera (Meusel and Kastner, 1990). Petit concluded that the chemical data were in agreement with the overall homogeneity of the subtribe.…”
Section: Tribe Cardueaementioning
confidence: 79%
“…This is borne out in work referred to by Petit (1999), of which we were unaware. Thus, a study of Carlina and Chamaeleon showed the presence of the C-glycosylflavones isovitexin, shaftoside, isoshaftoside, orientin, and unidentified di-C-glycosyl derivatives of apigenin and lute olin variously distributed in members of the two genera (Meusel and Kastner, 1990). Petit concluded that the chemical data were in agreement with the overall homogeneity of the subtribe.…”
Section: Tribe Cardueaementioning
confidence: 79%
“…Most populations grow in semi-natural calcareous grasslands, but the plant also occurs in quarries, coastal dunes and open pine forests (Verkaar and Schenkeveld 1984;Grime et al 1988;Meusel and Kä stner 1994). The probability of flowering increases with the size of the rosette (Klinkhamer et al 1991(Klinkhamer et al , 1992, and the age of flowering plants varies between 2 and at least 11 years (Watt 1981;Klinkhamer et al 1996;Rose et al 2002).…”
Section: Study Speciesmentioning
confidence: 98%
“…In Europe, the species is distributed in (sub-)oceanic to sub-Mediterranean regions from southern Italy (39 N) to southern Sweden (62 N). Because of habitat deterioration and fragmentation in the last decades, many populations are now small and isolated, particularly in the north-east of the distribution area (Meusel and Kä stner 1994).…”
Section: Study Speciesmentioning
confidence: 99%
“…Homologies of the synflorescence of Echinops L. and related genera are ex-tremely difficult to establish (Petit, 1988), as is usually the case with highly derived syncephalies (Stuessy and Spooner, 1988). A similar problem is posed by the complicated involucral structures of the Carlininae, which have been interpreted even as a third-order syncephalia in the genus Carlina L. (Meusel and Kohler, 1960;Meusel and Kä stner, 1994), an interpretation rejected by Petit (1988). In fact, contradictory results obtained by different authors in cladistic analyses of morphologic data (e.g., Karis et al, 1992versus Petit, 1997 could be partly attributed to different points of view in addressing the problem of homologies of the receptacular structures of Echinops, Carlina, and related genera.…”
Section: Introductionmentioning
confidence: 95%
“…With regard to life forms, Carlina falcata, from the Canary Islands, is an unarmed and shrubby plant, two very unusual features in a group formed mainly by spiny perennial herbs. This led Meusel and Kä stner (1994) to suggest that the Canarian species of Carlina were the oldest stock of the genus. However, all the analyses group in a very robust clade Carlina falcata and the widespread European spiny herbs Carlina lanata and C. vulgaris [BS ϭ 73%, DI ϭ 2 in the ITS analysis (Fig.…”
mentioning
confidence: 98%